Effects of adjuvant chemotherapy on recurrence rate in T1abN0M0 triple-negative breast cancer: A meta-analysis. (2020) - Yang, Zijian; Chen, Yonghua; Liu, Xiaoling; Cui, Junwei; Hu, Yibing; Wei, Wei
Highlights: Chemotherapy for small TNBC has been a controversy issue these years. Related studies were limited by small number and few had statistically significant results. We collected 9 studies in the last decade including more than 1000 patients and summarized a robust result which successfully passed sensitivity analysis and majority of publication bias testing. Our results revealed that adjuvant chemotherapy reduced recurrence rate for T1mi/a/bN0 TNBC, especially for T1bN0. Abstract: Purpose: Triple-negative breast cancer (TNBC) is known for its higher recurrence rate in short-term (3-5 years) follow-up and limited systemic therapeutic methods (chemotherapy). Current literature debates over whether chemotherapy should be given to TNBC with a very early disease stage (T1a/bN0). This meta-analysis aimed to compare short-term recurrence rate between patients receiving adjuvant chemotherapy or not for this population. Methods: We performed a comprehensive search in databases including PubMed, Web of Science, Embase, and Cochrane library from January 2008 to December 2019. Raw data on local or distance recurrence events was extracted, odds ratio (OR) values, 95% confidence interval (CI) values, and P values were then calculated. Results: 9 studies out of 426 were included in the meta-analysis. Our main results showed that breast cancer recurrence rate in T1a/bN0 TNBC patients receiving chemotherapy was significantly lower than those without chemotherapy (OR 0.54, 95% CI 0.37–0.78, P = 0.001). Similar results were detected in the T1b group (OR 0.45, 95% CI 0.26–0.78). The main result remained stable after sensitivity analysis. No significant publication bias was found. Conclusions: Our results revealed that adjuvant chemotherapy reduced recurrence rate for T1mi/a/bN0 TNBC, especially for T1bN0. The benefit of chemotherapy for T1mi/aN0 disease is still debated.